2011
DOI: 10.1099/vir.0.036459-0
|View full text |Cite
|
Sign up to set email alerts
|

Avian and mammalian reoviruses use different molecular mechanisms to synthesize their μNS isoforms

Abstract: Previous reports revealed that the M3 gene of both avian and mammalian reoviruses express two isoforms of the non-structural protein mNS in infected cells. The larger isoforms initiate translation at the AUG codon closest to the 59 end of their respective m3 mRNAs, and were therefore designated mNS. In this study we have performed experiments to identify the molecular mechanisms by which the smaller mNS isoforms are generated. The results of this study confirmed the previous findings indicating that the smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…The M 115 residue was determined to be the best candidate as M 94 is not conserved among all PRV isolates, and M 85 and M 169 are unlikely due to the sizes of the proteins generated. Post-translational cleavage to generate µNSC as shown for ARV µNS cannot be excluded, although the specific proteolytic cleavage site in the ARV protein is not conserved in PRV [2,33,53]. The different µNS size variants, i.e., full-length µNS and the 70 kDa variant with putative translation initiation at M 115 , may differ in their interactions with other PRV proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The M 115 residue was determined to be the best candidate as M 94 is not conserved among all PRV isolates, and M 85 and M 169 are unlikely due to the sizes of the proteins generated. Post-translational cleavage to generate µNSC as shown for ARV µNS cannot be excluded, although the specific proteolytic cleavage site in the ARV protein is not conserved in PRV [2,33,53]. The different µNS size variants, i.e., full-length µNS and the 70 kDa variant with putative translation initiation at M 115 , may differ in their interactions with other PRV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is considered the most common morphology type of orthoreoviral factories [21,32]. Gene segment M3 in MRV and avian orthoreovirus (ARV) are reported to produce two isoforms of the factory forming µNS protein in infected cells [33,34,35]. The second isoform is produced by different mechanisms in the two viruses; in MRV, µNSC is expressed by a second in-frame AUG (Met 41 ) while in ARV, post-translational cleavage in the N-terminal region releases µNSN [33,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggest the 58-kDa NS80 fragment is a cleavage product, and NS80 may be a multifunctional protein. μNSC in MRV, which lacks the first 40 amino residues of μNS, is also produced naturally during MRV infection (Lee et al, 1981), and its translation is initiated from an alternative site in M3 mRNA (Busch et al, 2011). Similarly, ARV μNSC was detected in infected cells, but the results of a recent study demonstrated that it originates from a single post-translational cleavage event that occurs near the amino terminus of μNS (Busch et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…μNSC in MRV, which lacks the first 40 amino residues of μNS, is also produced naturally during MRV infection (Lee et al, 1981), and its translation is initiated from an alternative site in M3 mRNA (Busch et al, 2011). Similarly, ARV μNSC was detected in infected cells, but the results of a recent study demonstrated that it originates from a single post-translational cleavage event that occurs near the amino terminus of μNS (Busch et al, 2011). Our results are consistent with these previous results and suggest that the smaller NS80 fragment shares the same post-translational modification mechanism with ARV μNS.…”
Section: Discussionmentioning
confidence: 99%